2012
DOI: 10.1038/npp.2011.335
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Fluoxetine Selectively Upregulates Dopamine D1-Like Receptors in the Hippocampus

Abstract: The dentate gyrus of the hippocampus has been implicated in mechanisms of action of selective serotonin reuptake inhibitors (SSRIs). We have recently demonstrated that the SSRI fluoxetine can reverse the state of maturation of the adult dentate granule cells and enhances serotonin 5-HT 4 receptor-mediated synaptic potentiation at the synapses formed by their mossy fiber axons. Here, we show that fluoxetine can induce long-lasting enhancement of dopaminergic modulation at the mossy fiber synapse. Synaptic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 57 publications
4
46
1
Order By: Relevance
“…The prominent frequency facilitation, presynaptic short-term plasticity that is characteristic of mature MF synapses, was greatly decreased in mutants (Figure 3G). These changes are very similar to the changes observed in mice treated with FLX, which exhibit a “dematurated” DG [33,38]. Taken together, these results suggest that the granule cells in SNAP-25 KI mice have physiological properties that are characteristic of immature cells.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The prominent frequency facilitation, presynaptic short-term plasticity that is characteristic of mature MF synapses, was greatly decreased in mutants (Figure 3G). These changes are very similar to the changes observed in mice treated with FLX, which exhibit a “dematurated” DG [33,38]. Taken together, these results suggest that the granule cells in SNAP-25 KI mice have physiological properties that are characteristic of immature cells.…”
Section: Resultssupporting
confidence: 78%
“…The iDG phenotype has been identified in alpha-isoform of calcium/calmodulin-dependent protein kinase II (αCaMKII) heterozygous knockout (HKO) mice [32,34-36], Schnurri-2 (Shn-2) KO mice [37], and chronic fluoxetine (FLX)-treated mice [33,38,39]. To elucidate the molecular mechanisms responsible for the iDG phenotype in SNAP-25 KI mice, DNA microarray analysis was performed using the hippocampi of mutant mice.…”
Section: Resultsmentioning
confidence: 99%
“…Antidepressants have been found to rescue AMPA dysfunction in chronically stressed animals (Kallarackal et al., 2013) and further increase AMPA phosphorylation and surface expression (Martinez-Turrillas et al., 2002, Svenningsson et al., 2002). Specifically, fluoxetine, a selective reuptake inhibitor, increases AMPA-induced currents in pyramidal cells via activation of D1 receptors in the prefrontal cortex (Bjorkholm et al., 2015) and reverses behavioral signs of depression by increasing them (Kobayashi et al., 2012). Future studies will be needed to delineate whether the alterations observed in hippocampal spine morphology may be restored within the CA1 via dopamine and glutamate-dependent antidepressant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies reveal Flx's additional effect on DA receptors, and levels of neurotrophic signaling (Kobayashi et al, 2012, Lesemann et al, 2012. In accordance to the delayed effects of antidepressant action, a crucial involvement of cyclic AMP regulatory element-binding protein (CREB) (Palmer et al, 1997, Chen et al, 2001 and non-monoamine-based antidepressants have been suggested (Berton and Nestler, 2006).…”
Section: Neurogenesis/monoamine/neurotrophin Hypothesis Of Antidepresmentioning
confidence: 92%